ANALISIS PELAKSANAAN PROGRAM PENCEGAHAN KECURANGAN (FRAUD) JAMINAN KESEHATAN NASIONAL DI PUSKESMAS KOTA SEMARANG - Zafirah Rizka; Septo Patria Jati; Syamsulhuda BM (Jurnal Kesehatan Masyarakat (Undip), 2018)
National Health Insurance (NHI) fraud is actions taken by the participants, BPJS Kesehatan officers, medicines and medical devices providers intentionally by obtaining financial benefits from the NHI program through fraudulent conduct that isn’t in accordance with the provisions. In 2017, 26 puskesmas in 14 provinces have fraud potential of their capita funds. The government is implementing NHI fraud prevention program at puskesmas, as stated in the PMK RI no. 36 Year 2015. This study aims to analyze the implementation of PMK RI no.36 year 2015 in the Implementation of NHI fraud prevention program in Puskesmas Semarang City. This research used descriptive qualitative method with purposive sampling criteria toward 5 main informants and 2 informant triangulation. Processing and data analysis based on validity and reliability with triangulation. The result of this research shows that the establishment of NHI fraud prevention team is late because of SK DKK legality weakness about NHI fraud prevention team, and commitment of team members. Funding sources have not been allocated specifically for this program and team members' ignorance on its. The absence of monev activities, the planning of target, performance, budget, and technical guidelines from Ministry of Health or Semarang’s specific regulation. And, SKB3 hasn’t give a clear direction. The main cause of this team late establishment is SK DKK legality weakness about NHI fraud prevention team that affect to commitment of team members. Ministry of Health is suggested to make technical guidance related to PMK no. 36 of 2015. Semarang government is suggested to improve the coordination across sectors, and strengthen SKK DKK with the Mayor Regulation, so the legality is stronger. DKK Semarang is suggested to increase commitment and performance of program implementation. Head of Puskesmas is suggested to socialize prevention of NHI fraud to subordinates. And BPJS Kesehatan is suggested to increase cooperation